2023
DOI: 10.3389/fgene.2023.1142938
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a prognostic model based on eight ubiquitination-related genes via machine learning and potential therapeutics analysis for cervical cancer

Abstract: Introduction: Ubiquitination is involved in many biological processes and its predictive value for prognosis in cervical cancer is still unclear.Methods: To further explore the predictive value of the ubiquitination-related genes we obtained URGs from the Ubiquitin and Ubiquitin-like Conjugation Database, analyzed datasets from The Cancer Genome Atlas and Gene Expression Omnibus databases, and then selected differentially expressed ubiquitination-related genes between normal and cancer tissues. Then, DURGs sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Hao et al (2023) (79) identified the ubiquitination-related genes differentially expressed in CC tumors. They selected those associated with overall survival and established a prognostic gene signature that includes RBBP4, SRM, GCH1, USP14, TRAIP, CBX4, VEZF1, and TOM1 genes.…”
mentioning
confidence: 99%
“…Hao et al (2023) (79) identified the ubiquitination-related genes differentially expressed in CC tumors. They selected those associated with overall survival and established a prognostic gene signature that includes RBBP4, SRM, GCH1, USP14, TRAIP, CBX4, VEZF1, and TOM1 genes.…”
mentioning
confidence: 99%